Working or stay-at-home mum? The influence of family benefits and religiosity - Ulrike Jäger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
It is a well-established fact that mothers' labour force participation reacts differently todifferent types of family benefits. It is also already well-known that cultural and religiousfactors have an impact on their labour force participation. But does the labour forcereaction to family benefits differ among more religious mothers? In this paper, I analysehow both factors benefits and religiosity interact when it comes to the decision concerninglabour force participation. Firstly, I present a theoretical model which predicts thatthis difference exists. Secondly, I test this prediction in a sample of pooled cross-sectiondata from 10 OECD countries using different measures to assess the extent of religiosity.There is evidence that religious mothers react less than non-religious mothers toincreases in family benefits. I also find important differences among various religiousaffiliations. These results imply that trends in religiosity should be considered whendesigning labour market policies.
Keywords: H20; J21; Z10; Z13; 330; Female labour force participation; public benefits; culture; family attitudes; Weibliche Arbeitskräfte; Mütter; Weltanschauung; Berufliche Integration; Arbeitsmarktpolitik; OECD-Staaten